Analisis N Dan P Pupuk Organik Cair Kombinasi DaunLamtoro Limbah Tahu Dan Feses Sapi - MARLINA, SUSI, Dra. Aminah Asngad, S.Si, M.Si (2016)
Liquid organic fertilizer is a solution containing various substances needed for plant growth. Liquid organic fertilizer can be derived from the rest of the kitchen waste, sewage, and waste bins foliage. Liquid organic fertilizer containing nutrients, phosphorus, nitrogen and potassium required by plants and can improve soil nutrients. Lamtoro leaf extract, waste tofu, and cow feces can be combined into a liquid organic fertilizer containing nitrogen, phosphorus, and potassium. The purpose of this study is to determine the content of nitrogen and phosphorus in liquid organic fertilizer made from extracts of leaves lamtoro, waste tofu, and cow feces. This research method using a completely randomized design (RAL) with two factors, a factor of 1: leaf extract combination lamtoro and waste out 82 ml + 168 ml (K1), 125 ml + 125 ml (K2), 168 ml + 82 ml (K3) and a factor of 2: cow feces volume 180 ml (I1), 360 ml (I2), 540 ml (I3). In this study showed the content of nitrogen (N) is highest at treatment K3I3 (lamtoro leaf extract 168 ml + 82 ml tofu waste + cow feces 540 ml) is 0.22%. While the results of the highest phosphorus content contained in K1I3 treatment (82 ml lamtoro leaf extract + the waste out 168 ml + 540 ml cow feces) is 0.20%. The conclusion that there was an effect of extract of leaves lamtoro, waste tofu, and cow feces to the elements nitrogen and phosphorus.